Entrepreneurial Ecosystems Place-Based Transformations and Transitions (International Studies in Entrepreneurship,, 2018)
This book features latest research insights into the study of the entrepreneurial ecosystem. The focus is on understanding its influence on the development of socially and physically defined 'places', and how these factors are related with each other. The book argues that regardless of how the concept of a 'place' is defined, be it cities, regions, nations or otherwise, the impact of new technologies will influence much of our business, social, and economic landscapes. Evidently, there is an increasing pressure on 'places' to embrace new opportunities for strategic development and confront complacency. The solution may very well be in creating and sustaining entrepreneurial ecosystems where entrepreneurial action thrives and innovation drives the new economy.